The Usage of Slang Words in ‘My Block’ Movie - Ni Wayan Sukarini; Sang Ayu Isnu Maharani; Byanca Vanessa Suwasdika (CV Wahana Publikasi, 2024)
This study aims to identify the various slang words featured in the movie “On My Block,” with a particular focus on those employed by the main character while also delving into their semantic nuances. This research contributes to a broader understanding of the usage of slang language, enriching the knowledge of listeners and viewers alike. The study employed in this study revolves around documentation. Data collection involved viewing the movie and meticulously documenting dialogues containing slang expressions used by the characters. The subsequent analysis draws upon Partridge’s framework for categorizing slang types, coupled with sourcing slang meanings from Partridge’s dictionary. The study adopts a multifaceted approach, encompassing both formal and informal methods to present the analytical findings. The research findings effectively address two critical facets of the research problem. Firstly, they categorize the slang words featured in the “On My Block” movie into three distinct types: Society slang, Cockney slang, and Public House slang. Secondly, the study elucidates the significance of these slang words in the context of the movie, shedding light on their functional roles within conversational exchanges.